Giardia intestinalis and nutritional status in children participating in the complementary nutrition program, Antioquia, Colombia, May to October 2006 (2009)
ABSTRACT: Giardia intestinalis infection is prevalent throughout the world and widely distributed in developing countries. In general, children display serious consequences to their state of health, including slow height-weight development; therefore, the main aim of this study was to determine the association between Giardia infection and the nutritional status of children who participate in the program of complementary feeding (Mejoramiento Alimentario y Nutricional de Antioquia (MANA) - Instituto Colombiano de Bienestar Familiar (ICBF)). A cross-sectional study examining the association of giardiasis with nutritional status was conducted. A total of 2035 children aged eight months to six years-old were studied. Data were collected using structured questionnaires, anthropometric measurements and laboratory analysis of blood and stool samples. Analysis of the results showed that 27.6% of children were infected with G. intestinalis, while 8.1% and 1.9% were mildly and significantly underweight, respectively, and 14.1% presented stunting. Giardiasis was statistically identified as a strong predictor of stunting in this study population.